Psychological impact of isotretinoin treatment in patients with moderate and severe acne - Šimić, Dubravka (Array, 2009)
Summary: Acne patients are subject to different degree of psychosocial distress. The emotional impact of acne vulgaris due to disfigurement caused by the disease is undisputed. Most common reactions to the acne are depression and anxiety. The use of isotretinoin, one of the most effective options in acne treatment, increases depression symptoms. The aim of this study was to investigate the psychological status of the patients with moderate to severe acne and to compare patients treated with isotretinoin with patients treated with vitamin C. A total of 85 patients suffering from acne vulgaris were included in the study. The results of this study do not find a significant correlation between the use of isotretinoin and the psychological effects of the drug